Trends in patients' overall satisfaction with healthcare delivery in Accra, Ghana - Stephen T. Odonkor; Charles Frimpong; Emmanuel Duncan; Carolyn Odonkor (AOSIS, 2019)
Background: Patient satisfaction represents a key marker for the quality of healthcare delivery and is critical for smooth functioning of the healthcare system. Aim: The aim of this study was to determine the levels of patient satisfaction with the quality of care they receive, and thus identify the key factors that influence patients' overall satisfaction with healthcare. Setting: The study was conducted across seven healthcare facilities in Greater Accra region. Methods: The study employed a cross-sectional design to obtain data from 417 respondents between 01 November 2017 and 31 January 2018. Patient satisfaction within the context and setting of this study refers to the extent to which patients are happy with the healthcare services they receive. Statistical analysis was performed using Statistical Package for the social Sciences (SPSS) version 23. Results: Female patients constituted 66.7% of the respondents, while 33.3% were male patients. Most of the participants had health insurance coverage (95.2%). Overall, 69.5% of the patients were satisfied with the level of care, 29.3% were somewhat satisfied and 1.2% were not satisfied. Female patients (86.0%) were more satisfied with the level of care they received compared to male patients (61.9%). Majority of the female patients (87.8%) indicated that they were treated with courtesy and respect. However, more than a half (51.8%) of male patients indicated they were not treated with courtesy and respect. Patient satisfaction negatively correlated with social status and age of the patients. Conclusion: Measurement of patients' satisfaction is important for healthcare delivery. It was clear from this study that there is still a gap in improving and managing patients' satisfaction and expectation. All stakeholders must get involved to ensure timely and satisfactory healthcare delivery to all patients.